Optimism, Resilience, and Psychological Well-Being among Female University Students - Attiya Saleem; Rimsha Irshad; Marium Idrees (Research Journal of Psychology, 2025)
Optimism, resilience, and psychological well-being are crucial for achieving academic success among university students. This study aimed to explore the interconnection between optimism, resilience, and psychological well-being specifically among female university students. Additionally, it identified the impact of resilience and optimism on psychological well-being. The research involved 300 female students from the Government Sadiq College Women University in Bahawalpur, Pakistan, utilizing a quantitative approach and a convenient sampling technique. Data collection involved questionnaires comprising informed consent and demographic information. The study employed the Revised Life Orientation Test (LOT-R) to gauge optimism, the Brief Resilience Scale to measure resilience, and the Warwick-Edinburgh Mental Wellbeing Scale (WEMWBS) to assess psychological well-being. The findings of the study reveal a significant correlation between resilience, optimism, and psychological well-being. These results carry substantial implications. Addressing optimism, resilience, and psychological well-being among female students can uncover the intricate relationship between optimism and psychological well-being while promoting resilient mindsets among university students.